Polyester film for graphite adhesive tape base

By incorporating specific-sized particles into the polyester resin layer and controlling the film thickness, the challenges of maintaining strength and workability in ultra-thin polyester films for graphite adhesive tapes are addressed, resulting in films suitable for demanding applications.

JP7666141B2Active Publication Date: 2025-04-22MITSUBISHI CHEM CORP
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2021093930
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-06-03
Publication Date
2025-04-22
Estimated Expiration
2041-06-03

AI Technical Summary

Technical Problem

Ultra-thin polyester films used as substrates for graphite adhesive tapes face challenges in maintaining winding ability and workability due to the presence of large particles, which can form voids and reduce film strength, especially when the film thickness is 1.5 μm or less.

Method used

Incorporating particles with an average size of 0.5 to 1.6 μm into the polyester resin layer and controlling the film thickness to achieve a ratio of 0.90 or more between the film thickness and particle size, while ensuring no gaps larger than 150 nm in the film cross-section, to enhance film strength and prevent void formation.

Benefits of technology

The solution enables the production of ultra-thin polyester films with improved winding and workability, maintaining strength and preventing film breakage even at thicknesses of 1.5 μm or less, making them suitable for applications requiring strong adhesive strength and thermal dispersibility.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007666141000002
    Figure 0007666141000002
  • Figure 0007666141000003
    Figure 0007666141000003
  • Figure 0007666141000001
    Figure 0007666141000001
Patent Text Reader

Abstract

To provide a novel polyester film for a graphite adhesive tape substrate, wherein the polyester film does not cause voids (cavities) and retains current strength while having excellent handleability.SOLUTION: A polyester film for a graphite adhesive tape substrate contains particles with an average particle size of 0.5-1.6 μm relative to a polyester resin layer. The relationship between a film thickness (t: μm) and an average particle size of particles (X: μm), (t / X), is 0.90 or more, with the film thickness (t) being 0.5-1.5 μm.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polyester film for use as a graphite pressure-sensitive adhesive tape substrate. [Background technology]

[0002] Polyethylene terephthalate (PET) film, a representative polyester film, especially biaxially oriented PET film, is widely used in a variety of fields, including industrial materials, optical materials, electronic component materials, and battery packaging materials, due to its excellent transparency, mechanical strength, heat resistance, and flexibility.

[0003] In recent years, in mobile terminal devices such as mobile phones, smartphones, and laptop computers, as well as electronic and optical components in digital cameras and digital video cameras, efforts have been made to make them thinner, lighter, and even to use paper displays while at the same time improving their functionality. For example, the main components of smartphones are becoming thinner in order to improve their functionality and portability. In addition, in the case of graphite sheets that disperse localized heat generated in the CPU of smartphones and laptops, the thickness of the base film used to fix the graphite sheet hinders the heat dispersion of the graphite, so the adhesive tape needs to be made thinner.

[0004] In some of the above applications, a tape to which an adhesive layer is transferred is used to make the product thinner, but in this case, the absence of a core material causes a problem of poor durability. Therefore, many ultra-thin double-sided tapes have been developed, and Patent Documents 1 and 2 disclose adhesive tapes having an adhesive layer on a 1-3 μm polyester film as a substrate. However, although the above document discloses the thickness configuration and breaking strength of the pressure-sensitive adhesive tape, and the configuration of the pressure-sensitive adhesive layer, it does not specifically disclose the base polyester film. In particular, in recent years, due to the increased thermal dissipation properties of graphite sheets, there is a demand for extremely thin double-sided adhesive tapes, for example, 6 μm or less, and in order to achieve the desired strong adhesive strength, it has sometimes been necessary to use an extremely thin polyester film, 1.5 μm or less, as the substrate. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2005-105212 A [Patent Document 2] JP 2007-169327 A Summary of the Invention [Problem to be solved by the invention]

[0006] Generally, when a polyester film is made thinner, large particles are usually contained in the film to improve winding properties. However, if the particle size is too large, the particles form voids in the film, which can cause problems when handling the film in situations where film strength is required. For example, when peeling off an adhesive tape with an adhesive layer on an extremely thin polyester film from an adherend, the film may break due to the insufficient strength of the film, due to the presence of voids (air gaps) in the film, which causes the film to be peeled off. In recent years, the clearance allowed for adhesive members has tended to become narrower, and this has been a serious issue as polyester films are becoming thinner.

[0007] The present invention has been made in consideration of the above-mentioned circumstances, and an object of the present invention is to provide a polyester film for a graphite pressure-sensitive adhesive tape substrate which not only maintains and improves winding property and workability, but is also suitable as an adhesive member requiring an ultra-thin film thickness, particularly 1.5 μm or less. [Means for solving the problem]

[0008] As a result of extensive investigations, the present inventors have found that the above-mentioned problems can be solved by incorporating particles having a specific particle size into a polyester resin layer and controlling the film thickness, and have completed the present invention as described below. That is, the present invention provides the following [1] to [5]. [1] A polyester film for use in a graphite pressure-sensitive adhesive tape substrate, comprising a polyester resin layer containing particles having an average particle size of 0.5 to 1.6 μm, wherein the ratio (t / X) of the thickness t (μm) of the polyester film to the average particle size X (μm) of the particles is 0.90 or more, and the thickness t of the polyester film is 0.5 to 1.5 μm. [2] The polyester film for use in a graphite adhesive tape substrate according to [1] above, characterized in that, when observed through a cross section of the film by SEM, there are no voids having a maximum diameter of 150 nm or more. [3] The polyester film for a graphite adhesive tape base according to [1] or [2] above, having a tensile strength of 245 MPa or more in at least one of the machine direction (MD) and the transverse direction (TD). [4] An adhesive tape for fixing graphite, comprising an adhesive layer on at least one side of the polyester film for a graphite adhesive tape base according to any one of [1] to [3] above. [5] The polyester film for a graphite pressure-sensitive adhesive tape substrate according to any one of the above [1] to [3], which is for use in electronic devices. Effect of the Invention

[0009] According to the present invention, it is possible to provide a polyester film for a graphite pressure-sensitive adhesive tape substrate which maintains or improves winding properties and workability and is suitable as an adhesive member requiring an ultra-thin film thickness, particularly a film thickness of 1.5 μm or less. [Brief description of the drawings]

[0010] [Figure 1] FIG. 2 is a schematic diagram of a cross section of the film of Example 1. [Diagram 2]FIG. 2 is a schematic diagram of a cross section of a film of Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Next, an example of an embodiment of the present invention will be described. However, the present invention is not limited to the embodiment described below.

[0012] <Polyester film> The polyester film of the present invention (hereinafter sometimes referred to as "the polyester film") is a polyester film for use in a graphite pressure-sensitive adhesive tape substrate, which contains particles having an average particle size of 0.5 to 1.6 μm, has a ratio (t / X) of the thickness t (μm) of the polyester film to the average particle size X (μm) of the particles of 0.90 or more, and has a thickness t of 0.5 to 1.5 μm. By having the above-mentioned configuration, winding properties and workability are maintained or improved even in the case of an ultra-thin film. The polyester film has excellent physical properties such as heat resistance, flatness, optical properties, strength, etc. The polyester film may be a single layer or a multilayer film having two or more layers with different properties (that is, a laminated film). The polyester film of the present invention, in the case of a single layer, is made of a single polyester resin layer and the particles are contained in the polyester resin layer, whereas, in the case of a multilayer film, it means that it is made of a plurality of polyester resin layers and any one of the polyester resin layers contains the above-mentioned particles. The polyester film may be a non-stretched film (sheet) or a stretched film. Of these, a stretched film stretched in a uniaxial or biaxial direction is preferred. Of these, a biaxially stretched film is more preferred from the viewpoint of balance of mechanical properties and flatness. Therefore, a biaxially stretched polyester film is even more preferred.

[0013] (polyester) The polyester, which is the main component resin of the polyester film, may be a homopolyester or a copolymer polyester. The main component resin means the resin having the largest mass ratio among the resins constituting the polyester film, and may account for 50 mass% or more, 75 mass% or more, 90 mass% or more, or 100 mass% of the resins constituting the polyester film.

[0014] The homopolyester is preferably one obtained by polycondensation of an aromatic dicarboxylic acid and an aliphatic glycol, such as terephthalic acid or 2,6-naphthalenedicarboxylic acid, or ethylene glycol, diethylene glycol, 1,4-butanediol, or 1,4-cyclohexanedimethanol. Representative examples of homopolyester include polyethylene terephthalate (PET) and polybutylene terephthalate (PBT).

[0015] On the other hand, when the polyester is a copolymer polyester, it is preferable that the polyester is a copolymer containing 30 mol % or less of a third component. Examples of the dicarboxylic acid component of the copolymer polyester include one or more of isophthalic acid, phthalic acid, terephthalic acid, 2,6-naphthalenedicarboxylic acid, adipic acid, sebacic acid, etc., and examples of the glycol component include one or more of ethylene glycol, diethylene glycol, propylene glycol, 1,4-butanediol, 1,4-cyclohexanedimethanol, neopentyl glycol, etc. Among these, the base material in the present polyester film is preferably polyethylene terephthalate, which contains 60 mol % or more, preferably 80 mol % or more of ethylene terephthalate units.

[0016] (Polyester polycondensation catalyst) Examples of the polycondensation catalyst used in polycondensing the polyester include antimony compounds, germanium compounds, aluminum compounds, titanium compounds, etc. Among these, at least one of antimony compounds and titanium compounds is preferred, and it is particularly preferred to use a polyester obtained by using a titanium compound. Therefore, the polyester film preferably contains at least one of an antimony compound and a titanium compound, and more preferably contains a titanium compound. By using the titanium compound, it is possible to reduce the number of metal-containing aggregates, so-called coarse foreign matter, in the film that originates from the titanium compound.

[0017] (particle) The polyester film of the present invention is characterized in that the polyester resin layer contains particles having an average particle size of 0.5 to 1.6 μm. By containing particles, it is possible to provide easy slippage and prevent scratches in each process. When particles are added, the type of particles to be added is not particularly limited as long as it is a particle that can provide easy slippage, and specific examples include inorganic particles such as silica, calcium carbonate, magnesium carbonate, barium carbonate, calcium sulfate, calcium phosphate, magnesium phosphate, kaolin, aluminum oxide, and titanium oxide, and organic particles such as acrylic resin, styrene resin, urea resin, phenol resin, epoxy resin, and benzoguanamine resin. Furthermore, the particles may be additive particles added to polyester, or precipitated particles obtained by precipitating and finely dispersing a part of a metal compound such as a catalyst during the polyester production process.

[0018] On the other hand, the shape of the particles to be used is not particularly limited, and any of spherical, blocky, rod-like, flat, etc. may be used. In addition, there is no particular limit to the hardness, specific gravity, color, etc. Two or more kinds of these particles may be used in combination as necessary. Moreover, it is an essential requirement that the average particle size of the particles used is 0.5 to 1.6 μm, preferably 0.8 to 1.6 μm, and more preferably 1.0 to 1.6 μm. By using particles having an average particle size in the above range, it is possible to impart an appropriate surface roughness to the polyester film and ensure good slipping properties and smoothness. In the case where the polyester film is multi-layered, for example, it is preferable to provide a surface layer and an intermediate layer as the polyester resin layer, and to incorporate particles in the surface layer. In this case, it is more preferable to form a multi-layer structure having a particle-containing surface layer, an intermediate layer, and a particle-containing surface layer in this order.

[0019] Furthermore, the content of particles in the polyester film is preferably 5% by mass or less, more preferably in the range of 0.0003 to 3% by mass, even more preferably 0.05 to 2% by mass, and particularly preferably 0.1 to 1% by mass. By setting the content of particles within the above range, it becomes easier to impart slipperiness to the film while ensuring the transparency of the film, and furthermore, even in the case of an ultra-thin film, it is possible to maintain or improve winding properties and workability.

[0020] In the present invention, a film having a moderately roughened surface is obtained, and in consideration of workability and processability, the two-dimensional average surface roughness (Ra) of the film surface is preferably 31 nm or less. When the two-dimensional average surface roughness (Ra) of the film is 31 nm or less, there is no excessive increase in thickness around the protrusions due to the particles on the film surface being too large. Therefore, the clearance allowed for the adhesive member is not exceeded, and sufficient narrowing can be accommodated. From the above viewpoints, it is more preferable that the two-dimensional average surface roughness (Ra) of the film is 28 nm or less. On the other hand, the lower limit of the two-dimensional average surface roughness (Ra) of the film surface is not particularly limited, but if it is 10 nm or more, winding properties and workability can be maintained or improved, making the film suitable for use as an adhesive member requiring an ultra-thin film thickness.

[0021] In the polyester film used in the present invention, the dynamic friction coefficient (μd) between the films is preferably 0.95 or less, more preferably 0.75 or less, and even more preferably 0.55 or less. When the dynamic friction coefficient (μd) satisfies the above range, wrinkles are less likely to occur during the winding process during film processing, and workability is improved. In order to adjust the dynamic friction coefficient of the film within the above range, it is necessary to control the unevenness present on the film surface, which can be achieved by formulating two or more types of fine particles with different average particle sizes and appropriately adjusting the content thereof, as necessary.

[0022] <Method of manufacturing the polyester film> As an example of the method for producing the present polyester film, a method for producing the present polyester film as a biaxially stretched film will be described below, although the present invention is not limited to the method for producing the present polyester film.

[0023] First, using a known method, raw materials, such as polyester chips, are fed into a melt extrusion device, heated to above the melting point of each polymer, and the molten polymer is extruded through a die and cooled and solidified on a rotating cooling drum to a temperature below the glass transition point of the polymer, thereby obtaining an unoriented sheet in a substantially amorphous state.

[0024] Next, the unoriented sheet is stretched in one direction by a roll or tenter type stretching machine, at a stretching temperature of usually 25 to 120° C., preferably 35 to 100° C., and a stretching ratio of usually 2.5 to 7 times, preferably 2.8 to 6 times. Then, the film is stretched in a direction perpendicular to the first-stage stretching direction at a temperature of usually 50 to 140° C. and a stretch ratio of usually 3 to 7 times, preferably 3.5 to 6 times. In the above stretching, a method in which the stretching in one direction is carried out in two or more stages can also be adopted.

[0025] After the stretching, the film is subsequently heat-set at a temperature of 130 to 270° C. under tension or under relaxation of 30% or less to obtain the present polyester film as a biaxially oriented film. By subjecting the present polyester film to heat-setting, the heat resistance and other properties can be improved.

[0026] (film thickness) The film thickness must be 0.5 to 1.5 μm. It is preferably 0.8 to 1.5 μm. If it is less than 0.5 μm, it is difficult to mold the film, and if it exceeds 1.5 μm, it is difficult to achieve the object of the present invention to obtain an extremely thin film that can be adapted to narrow design. From the above viewpoints, it is particularly preferable that the film thickness is in the range of 0.8 to 1.2 μm.

[0027] <Characteristics of this polyester film> (ratio (t / X) of film thickness t (μm) to average particle diameter X (μm)) The polyester film of the present invention uses an extremely thin film of 1.5 μm or less, so the presence of a small void (gap) may cause problems in the processing step. For example, when peeling off the polyester film with the adhesive layer from the adherend, the strength in the thickness direction may be insufficient. As a countermeasure against such problems, in the present invention, the ratio (t / X) of the film thickness t (μm) to the average particle size X (μm) of the particles is designed to be 0.90 or more. It has been found that such a design allows the particle surface to be covered with polyester resin, suppressing the occurrence of voids (gap) and imparting appropriate slipperiness to the film. From the above viewpoints, the ratio (t / X) of the film thickness t to the average particle diameter X is preferably 0.95 or more, more preferably 1.00 or more, and particularly preferably 1.05 or more. On the other hand, there is no particular upper limit, but in order to exert the effect of containing the particles, it is preferably 2.00 or less, more preferably 1.50 or less. In addition, when two or more different average particle sizes are used for the average particle size X used in the calculation of (t / X), the average particle size X is calculated by dividing the total average particle size by the number of particle types.

[0028] (Voids in film cross section) The polyester film preferably has no voids with a maximum diameter of 150 nm or more when observed through a cross section of the film by a scanning electron microscope (SEM). More preferably, the polyester film has no voids with a maximum diameter of 100 nm or more, and particularly no voids with a maximum diameter of 50 nm or more. The absence of such voids prevents the above-mentioned problem of insufficient strength in the thickness direction when the polyester film with the adhesive layer is peeled off from the adherend.

[0029] (Tensile strength) In order to improve the workability during film processing, the polyester film preferably has a tensile strength in at least one of the machine direction (MD) and the transverse direction (TD) of 245 MPa or more, more preferably 250 MPa or more. It is more preferable that the tensile strength in both the MD and TD directions is 245 MPa or more. There is no particular upper limit to the tensile strength, but it is usually 400 MPa or less. The tensile strength was measured by the method described in the Examples. In this specification, the machine direction (MD) is the running direction (or winding direction) of the film during film formation, and the transverse direction (TD) is the direction perpendicular to the MD.

[0030] (Adhesive layer) The polyester film of the present invention is used as a substrate for an adhesive tape, and an adhesive tape for fixing graphite having an adhesive layer on at least one surface of the polyester film also constitutes the present invention. The adhesive forming the adhesive layer of the graphite fixing adhesive tape of the present invention is not particularly limited, and can be appropriately selected from known adhesives such as acrylic adhesives, rubber adhesives, silicone adhesives, urethane adhesives, polyester adhesives, styrene-diene block copolymer adhesives, vinyl alkyl ether adhesives, polyamide adhesives, fluorine adhesives, creep property-improved adhesives, radiation curable adhesives, etc. The adhesives may be used alone, or two or more types may be used in combination, as necessary.

[0031] From the viewpoint of adhesive reliability, acrylic adhesives are particularly suitable for use as the adhesive. Acrylic adhesives contain an acrylic polymer as an adhesive component (base polymer) or main component, and may contain additives such as crosslinkers, tackifiers, softeners, fillers, antioxidants, and colorants as necessary. The acrylic polymer is prepared by using an alkyl (meth)acrylate ester as a main monomer component, and, if necessary, a monomer (copolymerizable monomer) that can be copolymerized with the alkyl (meth)acrylate ester. Examples of the alkyl (meth)acrylate ester include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, cyclohexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, decyl (meth)acrylate, dodecyl (meth)acrylate, myristyl (meth)acrylate, palmityl (meth)acrylate, and stearyl (meth)acrylate. These may be used alone or in combination of two or more.

[0032] Examples of the copolymerizable monomer include carboxyl group-containing monomers or anhydrides thereof, such as (meth)acrylic acid, itaconic acid, maleic acid, fumaric acid, crotonic acid, and isocrotonic acid; sulfonic acid group-containing monomers, such as sodium vinyl sulfonate; aromatic vinyl compounds, such as styrene and substituted styrene; cyano group-containing monomers, such as acrylonitrile; olefins, such as ethylene, propylene, and butadiene; vinyl esters, such as vinyl acetate; vinyl chloride; amide group-containing monomers, such as acrylamide, methacrylamide, N-vinylpyrrolidone, and N,N-dimethylacrylamide; hydroxyl group-containing monomers, such as hydroxyalkyl (meth)acrylate and glycerin dimethacrylate; aminoethyl (meth)acrylate and (meth)acryloylmorpholine; Examples of the copolymerizable monomer include polyfunctional copolymerizable monomers (polyfunctional monomers) such as triethylene glycol diacrylate, diethylene glycol diacrylate, ethylene glycol diacrylate, tetraethylene glycol diacrylate, neopentyl glycol diacrylate, 1,6-hexanediol diacrylate, trimethylolpropane triacrylate, pentaerythritol triacrylate, dipentaerythritol hexaacrylate, and divinylbenzene. The copolymerizable monomers can be used alone or in combination of two or more.

[0033] The acrylic polymer can be prepared by a conventional polymerization method such as solution polymerization, emulsion polymerization, or ultraviolet radiation polymerization.

[0034] (Adhesive layer thickness) The total thickness (after drying) of the adhesive layer provided on the polyester film for graphite adhesive tape substrate of the present invention (hereinafter, sometimes referred to as "base polyester film" or simply "base material") is preferably 1.0 to 4.0 μm. Here, the total thickness means the thickness of the adhesive layer when the adhesive layer is present only on one side of the substrate, and means the total thickness of the adhesive layers on both sides when the adhesive layer is present on both sides of the substrate. When the adhesive layer is present on both sides such as a double-sided adhesive tape, the thickness (after drying) of the adhesive layer on one side is preferably in the range of 0.5 to 2.0 μm. By satisfying the thickness (after drying) of the adhesive layer within the above range, it is possible to achieve both appropriate adhesive strength and processability. In the present invention, adhesive layers may be provided on both sides of the substrate polyester film depending on the application, or a polyester film with a single-sided adhesive layer obtained in the process may be used. As long as the thickness (after drying) of the adhesive layer provided on the base polyester film is within the above-mentioned range, the front and back surfaces of the film may have the same thickness or may have different thicknesses.

[0035] From the viewpoint of achieving both a thinner polyester film substrate and adhesive strength, it is preferable that the thickness ratio (t / (A+t)) of the polyester film to the total thickness (A) of the adhesive layer and the thickness (t) of the polyester film is 30% or less. Preferably, (t / (A+t)) is 25% or less, more preferably 20% or less, and even more preferably 15% or less. In addition, by satisfying the above range, it is possible to set the thickness of the adhesive layer to be thick, which increases the degree of freedom in design, and therefore has the advantage that the adhesive tape can easily exhibit the desired strong adhesive strength.

[0036] In the pressure-sensitive adhesive tape of the present invention thus obtained, the adhesive strength is preferably 2 N / 10 mm or more, more preferably 4 N / 10 mm or more, for the purpose of imparting durability to withstand use at high temperatures, such as in a car in summer, while the upper limit is not particularly limited, but is preferably 10 N / 10 mm or less from the viewpoint of handling.

[0037] <Application> The polyester film of the present invention is useful as a graphite adhesive tape substrate. That is, since the polyester film of the present invention is extremely thin, by using it as a substrate film for fixing a graphite sheet, the thickness can be reduced and the thermal dispersibility of the graphite is not hindered. In addition, it is possible to ensure a sufficient thickness of the adhesive layer in order to exert a desired strong adhesive force. The polyester film of the present invention and the graphite fixing pressure-sensitive adhesive tape using the same are suitable for use in electronic devices. For example, the graphite fixing pressure-sensitive adhesive tape can efficiently diffuse heat by being used near a heat source inside a mobile phone, a smartphone, a notebook computer, etc.

[0038] <Explanation of terms, etc.> In the present invention, the term "film" includes the term "sheet", and the term "sheet" includes the term "film". In the present invention, when it is described as "X to Y" (X and Y are any numbers), unless otherwise specified, it includes the meaning of "X or more and Y or less", as well as the meaning of "preferably larger than X" or "preferably smaller than Y". In addition, when it is stated that the amount is "X or more" (X is any number), it also means that the amount is "preferably greater than X" unless otherwise specified, and when it is stated that the amount is "Y or less" (Y is any number), it also means that the amount is "preferably smaller than Y" unless otherwise specified. EXAMPLES

[0039] The present invention will now be described in more detail with reference to examples, although the present invention is not limited to the examples described below.

[0040] <Evaluation method> The methods for measuring and evaluating various physical properties and characteristics are as follows.

[0041] (1) Intrinsic viscosity (IV) 1 g of polyester was precisely weighed, dissolved in 100 ml of a mixed solvent of phenol / tetrachloroethane = 50 / 50 (mass ratio), and measured at 30°C.

[0042] (2) Average particle size In the case of added particles The particle size distribution was measured by the sedimentation method based on the Stokes resistance value using a centrifugal sedimentation type particle size distribution analyzer, Model SA-CP3, manufactured by Shimadzu Corporation. In the case of precipitated particles The polyester film containing the particles is sandwiched between a preparation, dissolved, cooled, and observed under a microscope, and the image is used to measure the average particle size using a Leica image processor (Quantimet500+). The concentration of precipitated particles is determined by adding 1.0 liter of o-chlorophenol to 100 g of polyester, heating at 120°C for 3 hours, centrifuging for 40 minutes using a Hitachi Koki ultracentrifuge (55P-72), and vacuum drying the particles obtained at 100°C. When the particles are measured using a scanning differential calorimeter, if a melting peak corresponding to the polymer is observed, o-chlorophenol is added to the particles, and the particles are heated and cooled, and then centrifuged again. When the melting peak is no longer observed, the particles are deemed to be precipitated particles. Two centrifugation operations are usually sufficient.

[0043] (3) Film thickness (gravimetric method) The measurement was made using the weight, length, width and density of the sample according to the following formula. Thickness = (weight of sample) ÷ ((length of sample) × (width of sample) × (density of sample))

[0044] (4) Observation of film cross section using SEM The cross-section of the film was observed using a SEM (Hitachi High-Tech Corporation, model: FE-SEM SU8220) (observation field: 19 μm × 25 μm, magnification: 5000 times) to confirm the presence or absence of voids (air gaps) on the cross-section of the film, and if present, the maximum diameter (nm) of the voids (air gaps) was also confirmed. If there were voids with a maximum diameter of 150 nm or more, they were recorded as "present," and if not, they were recorded as "absent."

[0045] (5) Tensile strength, tensile elongation at break (5-1) Tensile strength For the polyester films (samples) obtained in the Examples and Comparative Examples, a tensile tester (Intesco Model 2001, manufactured by Intesco Corporation) was used to measure the tensile strength of the polyester films (samples) obtained in the Examples and Comparative Examples. The polyester films (samples) having a width of 15 mm were set in the tester so that the distance between the chucks was 50 mm in the room adjusted to a temperature of 25°C and a humidity of 50% RH, and the samples were pulled at a strain rate of 200 mm / min. The tensile strengths of the films in the machine direction (MD) and the transverse direction (TD) were calculated according to the following formula. Tensile strength (MPa) = F / A In the above formula, F is the load at break (N), and A is the original cross-sectional area of ​​the test piece (mm 2 ). Measurements were taken at five points each in the machine direction (MD) and transverse direction (TD) of the film, and the average value was calculated for each. (5-2) Tensile elongation at break For the polyester films (samples) obtained in the Examples and Comparative Examples, the same tests as for tensile strength were carried out, and the tensile elongation at break in each of the machine direction (MD) and the transverse direction (TD) of the film was calculated according to the following formula. Tensile elongation at break (%) = 100 × (L-L0) / L0 In the above formula, L is the gauge length (mm) at break, and L0 is the original gauge length (mm). Measurements were taken at five points each in the machine direction (MD) and transverse direction (TD) of the film, and the average value was calculated for each.

[0046] (6) Two-dimensional average surface roughness of the film (Ra) It was determined as follows using a surface roughness tester (SE-3500) manufactured by Kosaka Laboratory Co., Ltd. That is, a portion of reference length L (2.5 mm) was cut out from the film cross-sectional curve in the direction of the average line, and when the average line of this cut out portion is expressed as the x-axis and the direction of longitudinal magnification as the y-axis, as a roughness curve y=f(x), the value given by the following formula is expressed in [nm]. The two-dimensional average surface roughness was expressed as the average value of the two-dimensional average surface roughness of the sampled area obtained from 10 roughness curves obtained from the surface of the sample film. The tip radius of the stylus was 2 μm, the load was 30 mg, and the cutoff value was 0.08 mm. (Ra)=(1 / L)∫L0|f(x)|dx

[0047] (7) Measurement method for film friction coefficient (μs / μd) A film cut to 150 mm in the longitudinal direction and 15 mm in the transverse direction is fixed on a flat SUS plated plate 75 mm wide and 85 mm long. A film of the same size is placed on top of it, and one end is fixed to a load cell. A silicone rubber plate 12 mm long, 12 mm wide, and 3 mm thick is placed on the bottom of the center of the overlapped films, and a weight of 50 g is placed on top of it. The plated plate is run in the opposite direction to the load cell at 20 mm / min to measure the friction force, and the point where it has slid 10 mm from the start of sliding (static friction coefficient) (dynamic friction coefficient) is measured (μs / μd). The measurements were performed at room temperature of 23°C ± 1°C and humidity of 50 ± 0.5% RH.

[0048] (8) Workability To improve the flatness during film processing, a strength of 245 MPa was applied to the film and the film was stretched, and the condition was judged. (Judgment criteria) A: The film does not break. ×: The film breaks.

[0049] (9) Narrow space design support When double-sided adhesive tape is designed so that the thickness of the adhesive layer on one side is 2.0 μm in order to be applied to parts where the clearance between parts is 5.5 μm or less, the product is judged based on whether it can accommodate that clearance, with those that can be marked as "O" and those that cannot be marked as "X."

[0050] The raw materials of the polyester films in the respective Examples and Comparative Examples are as follows. <Polyester (A)> A polyethylene terephthalate homopolymer with an intrinsic viscosity of 0.67. <Polyester (B)> A polyethylene terephthalate homopolymer with an intrinsic viscosity of 0.63. <Polyester (C)> A polyethylene terephthalate homopolymer with an intrinsic viscosity of 0.63, containing 0.5% by mass of organic particles (divinylbenzene-ethylstyrene-methacrylic acid-styrene copolymer) with an average particle size of 0.8 μm. <Polyester (D)> A polyethylene terephthalate homopolymer having an intrinsic viscosity of 0.63 and containing 1.0% by mass of calcium carbonate particles with an average particle size of 1.0 μm. <Polyester (E)> A polyethylene terephthalate homopolymer having an intrinsic viscosity of 0.63 and containing 0.4% by mass of calcium precipitate particles having an average particle size of 1.9 μm.

[0051] [Example 1] The mixed raw material, in which polyesters A, B, C, and D were mixed in proportions of 20 mass%, 29 mass%, 40 mass%, and 11 mass%, respectively, was fed to an extruder, melted at 285°C, and then extruded onto a cooling roll set at 25°C and cooled and solidified to obtain an unstretched sheet. Next, the film was stretched 4.0 times in the machine direction (MD) at a film temperature of 86°C using the roll peripheral speed difference. This machine-stretched film was introduced into a tenter and stretched 4.2 times in the transverse direction (TD) at 97°C. After heat treatment at 224°C, a polyester film was obtained that was relaxed by 2.0% in the transverse direction and had a thickness of 1.0 μm.

[0052] [Examples 2 and 3, Comparative Examples 1 to 3] A polyester film was obtained in the same manner as in Example 1, except that the conditions were changed as shown in Table 1.

[0053] [Table 1]

[0054] The polyester film of Example 1 is believed to have a relationship between film thickness and particle size as shown conceptually in FIG. 1, while the polyester film of Comparative Example 1 is believed to have a relationship between film thickness and particle size as shown conceptually in FIG. 2. It is believed that the difference in the relationship between film thickness and particle size causes the difference in the results, as shown in Table 1. Among them, in particular, in Examples 1 and 2, the film workability was good in comparison with the comparative examples, despite the use of fine particles with an average particle size of less than half that of the particles conventionally used. Furthermore, there were no voids in the film, and the risk of film breakage was significantly reduced. In the ultra-thin film field, where the film thickness is in the range of 0.5 to 1.5 μm, the presence of voids in the film can cause the film to break. This invention proposes a solution to this problem by focusing on the ratio (t / X) of the film thickness t (μm) to the average particle size X (μm) of the particles, starting from the idea of ​​supporting the particles themselves with polyester resin. [Industrial Applicability]

[0055] The polyester film of the present invention can be suitably used for fixing electronic and optical components in mobile terminal devices such as mobile phones and PDAs, digital cameras and digital video cameras, and as a substrate for adhesive tapes for graphite sheets even when there is a very thin clearance, and the industrial value of the present invention is high.

Claims

1. A polyester film containing particles having an average particle size of 0.5 to 1.6 μm in a polyester resin layer, wherein the ratio (t / X) of the thickness t (μm) of the polyester film to the average particle size X (μm) of the particles is 0.90 or more, and the thickness t of the polyester film is 0.5 to 1.5 μm; A polyester film for use as a graphite adhesive tape substrate, characterized in that a cross-section of the film is observed by SEM to be free of voids having a maximum diameter of 150 nm or more.

2. 2. The polyester film for a graphite pressure-sensitive adhesive tape substrate according to claim 1, which has a tensile strength of 245 MPa or more in at least one of a machine direction (MD) and a transverse direction (TD).

3. 3. An adhesive tape for fixing graphite, comprising the polyester film for use as a graphite adhesive tape substrate according to claim 1 or 2, and an adhesive layer on at least one surface of the polyester film.

4. 3. The polyester film for a graphite pressure-sensitive adhesive tape substrate according to claim 1, which is for use in electronic devices.

Citation Information

Patent Citations

  • Double-sided adhesive tape or sheet and method for producing them

    JP2005105212A

  • Double-sided adhesive tape

    JP2007169327A

  • Polyester film for double-sided adhesive tape

    JP2012135951A

  • Double-sided pressure-sensitive adhesive tape

    JP2012136634A

  • Double-sided self-adhesive tape

    JP2012224730A